MODEL OF IMPROVING HUMAN RESOURCE PERFORMANCE THROUGH SELF EFFICACY SOCIAL COMEPTENCE IN THE CONTEXT OF ISLAMIC WORK ETHICS - Wisnu Ardyanto; Widodo Widodo (UNISSULA, 2017)
This study aims to examine the effect of self efficacy and social competence on HR performance and in moderation of Islamic work ethic. The research problem is how to improve the performance of human resources through self efficacy and social competence with moderation of Islamic work ethic. The sampel of this research was the employees of the Department of Regional Finance of Semarang Regency consisting of 102 respondents. Regression analysis was done with Statistical Package Social Science (SPSS) software, and it was used also to analyze the data. The result of the analysis showed that self efficacy and social competence have a significant effect on HR performance with moderation of Islamic work ethic. These empirical findings indicate that self-efficacy has a significant effect on HR performance; Social competence has a significant effect on HR performance; social competence has significant effect on self efficacy; Islamic work ethic moderates the effect of competence on self efficacy; Islamic work ethic moderates the effect of self efficacy on HR performance; and Islamic work ethic moderates the effect of social competence on HR performance.Keywords: Self Efficacy, Social Competence, Islamic Work Ethics and HR Performance